Efecto de la aplicación del belgran (Bensulfuron-methyl) en el control de coquito(Cyperus rotundus) en el cultivo de caña de azúcar (Saccharun officinarum) en el CINCAE Cantón el Triunfo - Quiridumbay Tixe, Pastor Giovanny (2012)
A research was carried out in the Sugar Cane Research Center of Ecuador (CINCAE). The experimental center is located in the Canton “El Triunfo”, Guayas Province. The research started in February and the objectives were the following: 1. Determine the efficient doses of Belgran Herbacide over the cyperaceous weeds present in the sugarcane crop. 2) Establish Belgran selectivity in the sugar cane crop and, 3) Compare cost production among treatments. A complete block design (DBCA) with four treatments and four replicates was used to make a statistic analysis. The treatments were 1) Control (without herbicide); 2) Krismat (2.00 kg ha-1) + Agral (0.15 lt ha-1); 3.) Belgran (0.10 kg ha-1) + Agral (0.15 lt ha-1); 4.) Belgran (0.15 kg ha-1) + Agral (0.15 lt ha-1). There was not herbicide effect in the agronomic variables such as sprouting and plant population without statistic differences. Nevertheless, there was a significant effect of herbacides over the weeds population, especially treatment 2 (Krismat (2.00 kg ha-1) + Agral (0.15 lt ha-1)); which did the best control over the cyperaceas weeds. Despite it showed a slightly toxicity in some plants this disappeared throughout the days. The economical analysis showed that treatments 2 and 4 (Krismat (2.00 kg ha-1) + Agral (0.15 lt ha-1) and Belgran (0.15 kg ha-1) + Agral (0.15 lt ha-1), respectively) were almost similar; however, the treatment 2 was a little bit higher. After the analysis of this research related with the hypothesis that “The implementation of Belgran is effective to control Cyperus rotundus (coquito) and does not affect the sugar cane plants”, it is rejected because the herbicide effectiveness of Belgran did not show any control in the sugar cane plants.